Mycoplasma pneumoniae, Chlamydophila pneumoniae, Pneumocystis jirovecii and herpes infection in children with recurrent respiratory diseases - M. K. Khadisova (Alʹmanah Kliničeskoj Mediciny, 2017)
Rationale: Acute respiratory disorders (ARD) have the highest proportion among infectious disease in children. Despite the fact that serological diagnostics of Mycoplasma pneumoniae, Chlamydophila pneumoniae, Pneumocystis jirovecii, herpes simplex virus type 1 (HSV-1) and type 2 (HSV-2), Epstein-Barr virus (EBV), cytomegalovirus (CMV), human herpesvirus type 6 (HHV-6) has been available for many years, up to now some objective limitations exist that hinder reliable differentiation between the viral carriage, past or current infection. There are no widely accepted guidelines that would suggest unified strategies for diagnosis and what is of utmost importance, for therapeutic intervention on a  case-to-case basis. The rationale for this study was based on underestimation of the burden of these infections in children with prolonged periods of cough and recurrent ARDs, as well as the necessity to further develop diagnostic and management strategies.Aim: To determine causative role of M. pneumoniae, P. jirovecii, C. pneumoniae, HSV-1, -2, EBV, CMV, HHV-6 in children with recurrent ARDs hospitalized to an in-patient unit.Materials and methods: We examined 50 children with recurrent ARDs aged from 1 to 7 years who were hospitalized with an acute respiratory infection. Laboratory assessments included determination of the markers of infections caused by M. pneumoniae, P. jirovecii, C. pneumoniae, HSV- 1, -2, EBV, CMV, HHV-6 by means of polymerase chain reaction, immunoenzyme analysis, and indirect immunofluorescence reaction.Results: Markers of mycoplasma, chlamydial, pneumocystic infection, as well as HSV-1, -2, EBV, CMV, HHV-6 were found in 84% (42 / 50) cases. Active infection (acute or active persistent) was found in 38% (19 / 50) patients. The most prevalent was pneumocystic infection diagnosed in 12 (24%) patients; one fifth of all patients had mycoplasma (in 10 (20%) of cases), whereas herpetic and chlamydial infections were less frequent (4 (8%) and 1 (2%) of cases, respectively). Twelve (24%) patients had a single infection, while the others had mixed infections.Conclusion: We were able to confirm the possibility of combined M. pneumonia / P. jirovecii infection (8%) in children with recurrent ARDs and history of longstanding cough; this is important for an assessment of efficacy of causative treatment. Measurement of serum titers of specific immunoglobulins M and G along with DNA/antigens of potential causative organisms can be sufficient to choose specific antibacterial treatment of obstructive bronchitis and pneumonia in children with the history of longstanding cough and recurrent bronchial obstruction.